Comparative "ex vivo" study on working length determination using six apex locators - Leonardo Tracchegiani; Stefan Manea; Claudia Valentina Lungu; Sinziana Adina Scarlatescu; Paula Perlea; Anna Maria Pangica (Amaltea Medical Publishing House, 2023)
The aim of this study was to analyse the accuracy, precision, and consequently the reliability of five traditional apex locators (AL) and one integrated AL in determining working length (WL). Materials and Methods: The lengths of 15 extracted human teeth were measured with six ALs (Dentaport Root ZX, Dual Pex Micro Mega, Root ZX mini, Elements Diagnostic, Woodpex III, and E-connect S) and with digital radiographs (RVG). Electronic measurements were compared with each other and with radiographic measurements under the same experimental conditions. Results. Repeated measures ANOVA showed a significant difference between the radiographic and the electronic method. The Root ZX achieved the best accuracy and precision in determining the location of the apical foramen compared to other ALs. Conclusions. ALs are the most reliable method and superior to radiologic methods to determine the WL. Further studies should be performed to assess the differences between different types of ALs.